Type 2 diabetes mellitus and nonvalvular atrial fibrillation in Mexico: national registries raise a red flag - Manlio F. Márquez-Murillo; Eduardo Brenner-Muslera; Diana L. Rodríguez-Carrillo; César A. Chua-López; Margarita Torres-Tamayo (Permanyer, 2023)
Type 2 diabetes mellitus (T2DM) is one of the most common chronic diseases worldwide and is highly prevalent in Mexico, as 10.2% of the adult population harbors this condition. T2DM is usually associated with cardiovascular comorbidities, including arrhythmias. Metabolic impairment is one of the mechanisms that contribute to tissue remodeling that affects atrial structure, and concomitant, the cardiac conduction system, both could result in atrial fibrillation (AF). AF is estimated to affect more than a half million Mexicans, and its incidence is expected to keep rising. According to national registries, T2DM is present in 28.4% of Mexican patients with AF and the coexistence of both diseases is associated with a higher risk of stroke. In clinical practice, the CHA2DS2-VASc risk score is useful for stroke risk stratification in patients with AF to facilitate the adequate use of anticoagulation therapy. T2DM is among the items of the CHA2DS2-VASc score because it correlates with an intrinsic prothrombotic state. In this narrative review, we present information that highlights the need for optimal glucose control and adequate anticoagulation in subjects with T2DM and AF.